Linguoculturology as a complex field of scientific knowledge - Kadirova Barno Raimovna (Zien Journals, 2022)
The article discusses the specifics of the methodology of linguacultural. The possibility of linguacultural and the role as an independent section in linguistics are determined.
Keywords: linguistics; cultural studies; linguacultural; language